FAKTOR FAKTOR PENYEBAB PERGESERAN PERAN PEMANGKU ADAT DALAM PEMERINTAHAN DESA DI DESA BANJAR BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Purnama, Riska Tri; Erlinda, Sri; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study aims to know the role of stakeholders the custom in the village and the factors that cause a shift in the role of stakeholders the custom in the village in the village of Banjar Benai the district Benai of Kuantan Singingi.